Potentiometric Studies on Chelation of Cu(II), Ni(II), Co(II) and Fe(II) with o-Vanillinsemicarbazone - S. Jha, Chandra (Asian Journal of Chemistry, 2010)
Chelate formation of Cu(Il), Ni(Il), Co(II) and Fe(ll) with o-vanillinsemicarbazone in H2O-DMF medium (1 :1) at constant ionic strength (μ = 0.1 M KNO3) and at constant temperature of 25 ± 0.1 °C has been studied potentiometrically. The proton-ligand and metal-ligand stability constants were determined by Irving-Rossotti pH-metric titration technique. The results were discussed in details with reference to the results already reported in the literatures. The order of stability constant with respect to metal ions folIowed the natural order.